p21 regulates the migration and polarization of macrophages in diabetic tooth extraction wound by regulating periodontal ligament fibroblasts - ZHU Jiayu; YI Zimei; CHEN Siyi; DING Shuwen; YAN Jiayu; WU Junhua (Kouqiang hemian waike zazhi)
[Objective:] To explore the expression of cyclin-dependent kinase inhibitor 1A (CDKN1A/p21) in the healing process of tooth extraction wounds in diabetic mice and the effect on migration and polarization of macrophages. [Methods:] C57BL/6 male mice were selected to construct a model of diabetes mellitus and the right maxillary first molar was removed. The changes of bone tissue at 1, 3, 7 and 14 days after tooth extraction were observed and recorded by Micro-CT. The mRNA expression changes of p21, C-X-C motif chemokine ligand 14 (CXCL14) and the macrophage polarization markers in tissue samples were detected. In addition, real-time quantitative polymerase chain reaction (RT-qPCR) was used to detect the mRNA expression levels of p21 and CXCL14 in human periodontal ligament fibroblasts (hPDLFs) stimulated by high glucose in vitro, and the cell migration experiment was used to observe the changes in the migration ability of macrophages RAW264.7. CXCL14 protein was used to stimulate macrophages for 24 h, and its effect on the polarization of macrophages was verified by RT-qPCR. [Results:] Compared with the control group, the healing process of the tooth extraction wound was delayed in the experimental group. The mRNA expression of p21 in tissue was significantly increased on the third day after surgery, and the mRNA expression of CXCL14 showed the same trend (P<0.05). Meanwhile, the mRNA expression of M2 macrophage markers arginase-1 (ARG-1) and cluster of differentiation 206 (CD206) in tooth extraction callus tissue of diabetic mice increased synchronously on the third day after surgery (P<0.01). After high glucose stimulation of hPDLFs, the mRNA expression levels of p21 and CXCL14 increased. CXCL14 can increase the migration ability of macrophages and promote the M2 phenotype transformation. The expression of CXCL14 mRNA in hPDLFs was decreased by using the p21 small molecule inhibitor UC2288. [Conclusion:] During the healing process of tooth extraction wounds in diabetic mice, hPDLFs with high expression of p21 can promote macrophage migration and M2 polarization by secreting CXCL14.